Single vs. swarm detection of microparticles and exosomes by flow cytometry - Van Der POL, E.; Van GEMERT, M. J. C.; STURK, A.; NIEUWLAND, R.; Van LEEUWEN, T. G. (Journal of thrombosis and haemostasis, 2012)
See also Harrison P, Gardiner C. Invisible vesicles swarm within the iceberg. This issue, pp 916‐8. Summary. Background:  Microparticles and exosomes are cell‐derived vesicles and potential biomarkers for disease. Recently, the Scientific Standardization Committee collaborative workshop of the ISTH initiated standardization of vesicle detection by flow cytometry with polystyrene beads. Because polystyrene beads have different optical properties from biological vesicles, and because the mechanisms causing the detection signal are incompletely understood, there are contradictions between expected and observed results. Objectives:  To develop a model with which to relate the detection signal of a flow cytometer to the diameter of vesicles and clarify observed discrepancies. Methods:  We combined measurements of polystyrene and silica beads with an estimated refractive index of vesicles and performed Mie calculations of light scattering. Results:  We established the relationship between measured light scattering and the diameter of vesicles. The Megamix gating strategy proposed by the Scientific Standardization Committee selects single vesicles and cells with diameters between 800 and 2400 nm when applied on the forward‐scattering detector of regular flow cytometers. Nevertheless, we demonstrated that, irrespective of the applied gating, multiple vesicles smaller than 220 nm or multiple 89‐nm silica beads were counted as a single event signal at sufficiently high concentrations. Conclusions:  Vesicle detection by flow cytometry is attributed to large single vesicles and swarm detection of smaller vesicles; that is, multiple vesicles are simultaneously illuminated by the laser beam and counted as a single event signal. Swarm detection allows the detection of smaller vesicles than previously thought possible, and explains the finding that flow cytometry underestimates the concentration of vesicles.